2015
DOI: 10.1111/ajr.12248
|View full text |Cite
|
Sign up to set email alerts
|

Tele‐Derm National: A decade of teledermatology in rural and remote Australia

Abstract: This study identified some of the common dermatological complaints presenting to rural and remote primary care doctors in Australia. The unique addition of professional development in Tele-Derm can be used as an adjunct to advice provided to the rural doctors seeking advice for patient management.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(46 citation statements)
references
References 37 publications
0
45
0
1
Order By: Relevance
“…Several studies have demonstrated the utility of teledermatology, or more specifically store-and-forward applications. These studies have ranged from demonstrating improved access to dermatologic care in medically underserved areas [11][12][13] to shortening consult times in inpatient settings, 14 to providing patients with direct to consumer teledermatology services. 15 Moreover, provider satisfaction has also been shown to be high using store and forward applications.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have demonstrated the utility of teledermatology, or more specifically store-and-forward applications. These studies have ranged from demonstrating improved access to dermatologic care in medically underserved areas [11][12][13] to shortening consult times in inpatient settings, 14 to providing patients with direct to consumer teledermatology services. 15 Moreover, provider satisfaction has also been shown to be high using store and forward applications.…”
Section: Discussionmentioning
confidence: 99%
“…Not only does video conferencing via a synchronous system rely on the treating doctor, dermatologist, and patient being available simultaneously, it also requires additional and more complicated infrastructure to function (Byrom et al, 2016). Most notably, wide bandwidth communication and expensive video conferencing technologies (e.g., cameras,) are both necessary to achieve a consultation of adequate quality.…”
Section: Synchronous Systemsmentioning
confidence: 99%
“…For photos to be of good quality, they must be clear, demonstrate the anatomical distribution of lesions, and include a close-up to show the detail required for an accurate diagnosis (Byrom et al, 2016). The frequency of poor quality images used in asynchronous tele-dermatology systems has led many researchers to suggest that imaging training programs and guidelines be introduced (Lasierra et al, 2012, Landow et al, 2014, Wilson and Maeder, 2015).…”
Section: Asynchronous Systemsmentioning
confidence: 99%
“…As is observed with most medical specialties, dermatologists tend to practise in large metropolitan areas. Hence, for many patients substantial travel (and associated costs) is required to access specialist dermatological care . Additionally, there is a demand for dermatological care and the demand is expected to increase.…”
Section: Introductionmentioning
confidence: 99%